The image of a tent in turkic ethnic-epic thinking (based on "kitabi-dede gorgud") - NİZAMİ (Uluslararası Türk Lehçe Araştırmaları Dergisi)
The tent was considered one of the most important elements of the Turkic-ethnic cultural system. Because, mainly for the Turks who lead a nomadic lifestyle, a place of residence that can be built and dismantled quickly was more comfortable. There were different types of this settlement structure. "Dade Gorgud" has a tent home, a white house, a room, a tent, a room, a shed, a bargah, etc. described by names. At the same time, the tent symbolized not only a place of residence, but also a model of the world, an artistic expression of mythological thought. The belief and way of thinking of the Turks is also reflected in their tent tradition. This in turn shows that the tent is one of the most important elements of Turkish culture. While the tent symbolized the small state order - the family in Turkic thought, it also symbolized the world model in the archaic belief of the Turk in a broad sense. In his epic thinking, the Turk used the tent as a metaphorical means of understanding the world. The structure, poles, and design of the tent were reminiscent of the world. The tent built by the Turk also contained the four mother elements (fire, water, air, earth) which are considered the beginning of life. "Building the tent above the sky and the grass" shows that it is related to the element of earth, and the presence of a hearth inside it, called "gorglug", indicates that it is related to the element of fire. On the upper side of the tent, the hole that ensures easy entry of air and easy exit of smoke connects it with the element of air. Water was always considered the most important source of life for Turkic tribes.